Pengembangan Bahan Ajar Matematika untuk Kelas V SD Berbasis Permainan Tradisional Rakyat Daerah Riau - Sari, Eka Puspita; Roza, Yenita; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The analysis of mathematic text book for 5th grade of elementary school showed that it had some limitation in term of concept, media, and language. This research aim to develop suplement text book tobe used with main textbook provided by government. This book is developed based on traditional grames of Riau This research used Research and Development method with a model of Plomp. The study was started by analyzing mathematic elementary school textbooks that is used in 5th grade of elementary school and develop a new mathematic learning material based on traditional games of Riau.Traditional game used were gasing, besimbang, guli, congkak, setatak, and ligu.The development of mathematic learning material were conducted by: 1)Analyzingbasic competence and main competence of 2013 curriculum that match with traditional games of Riau; 2)Collecting and designing learning material content; 3)Developing mathematic learning material; 4)Testing, evaluating, and reviewing the mathematic learning material for 5th grade based on traditional games of Riau. Product of this research is mathematic learning material which contain learning activities in mathematic that match with traditional games of Riau The product of this research was tested to 30 students of 5th grade in elementary school. Analysis technique that is used is the quantitative descriptive analysis. The result of expert assessment showed that mathematic learning material based on traditional games of Riau is valid in ?high? category with an skor average was 3.38. Based on the result of experiments to 30 students in 5th grade of elementary school,it can be concluded that mathematic learning material has practicalty from the achievement and response of quetioner with the averagerating score of 93%. The textbook as the product of this research can be used as supplement book in teaching mathematic in 5th grade of elementary school.Key words: mathematic student textbook, traditional games of Riau, Research and Development